Analysis of 190 Female Patients after Appendectomy - Abdulrahman M. Alotaibi; Leena H. Moshref; Rana H. Moshref; Lina S. Felemban (Hindawi Limited, 2021)
This study is a retrospective cohort review carried out at a single, private tertiary center. We included 190 female patients who underwent surgery for acute appendicitis between January 2016 and December 2018. Two groups of patients were analyzed based on the pregnancy. The main outcome measures were complication rate and risk of abortion during or after surgery. Out of 190 female patients, eight of them were pregnant (4.2%). The pregnant group more significantly underwent ultrasound investigation compared to the nonpregnant group. Complicated appendicitis present in two pregnant patients at advanced gestational age was not statistically significant from nonpregnant. Laparoscopic appendectomy was performed in 6/8 (75%) of pregnant compared to 158/182 (87%) in nonpregnant (p = 0.415). Compared to the nonpregnant, the pregnant group has a more fecolith, positive peritoneal fluid culture, and wound infection, with E. coli more frequently isolated in 25%. None of the pregnant patients had an abortion, preterm labor, or mortality during or after surgery. In conclusion, laparoscopic appendectomy is a low-risk operation for pregnant with acute appendicitis.